Current concepts and practical applications for recovery, growth, and peak performance following significant athletic injury - Brooks, T. J.; Bradstreet, T. C.; Partridge, J. A. (Frontiers in Psychology, 2022)
For decades, physicians, athletic trainers, and other health care professionals have worked to standardize the recovery process following injury to enhance patient outcomes and to help set appropriate goals for return to competition. Traditionally, these efforts have focused primarily on physical and/or physiological aspects of healing with little consideration for psychological aspects. Concurrently, mental health professionals who work with athletes have developed strategies to enhance performance and minimize negative influences of mental aspects of recovery while promoting approaches that include mental as well as physical recovery. Several strategies have emerged that further encourage a multi-faceted and interdisciplinary approach when helping injured patients return to participation. While important in a healthy population, the practical applications of these strategies are likely more critical for an athlete working through the recovery process with an ultimate goal of returning to competition. Despite these realities, both practical experience and a dearth of literature point to the traditional athletic healthcare providers` common focus on physical aspects of recovery and psychological professionals` focus primarily on mental aspects has resulted in sub-optimal outcomes compared to the likely benefits of an integrated approach. This article is intended to characterize current concepts in the fields of sport psychology and mental health concerning the importance of mental aspects of recovery in returning to play. Next, the authors will examine how modern theories can influence practice and discuss how these strategies can be effectively integrated and leveraged to enhance recovery and the athlete`s enjoyment of the rehabilitation and ultimately restoration process.